THE USE OF ILLOCUTIONARY ACT IN “WONDER” MOVIE BY RJ. PALACIO - Fitri Kharisma Putri; Ana Mariana (Universitas Muhammadiyah Gorontalo, 2018)
Language is a core of communication and in pragmatics, it is analyzing the information about the development of language and knowledge of language in general and it is related with human language and its context. Pragmatics is concerned with the study of meaning that communicated with the speaker and interpreted by a listener. Context also holds the important rules and cannot be separated in learning pragmatics itself. Therefore, to learn and understand the meaning and it’s context of spoken between speaker and hearer in an utterance, then learning the speech act and it’s parts is one of the important things. This research discusses the use of illocutionary acts in “Wonder” movie. The focus analysis on this research is not only on the main character but on the whole conversation from each character at the movie by classified it into five types by using John Searle’s (1975) theory. The data of illocutionary that appears on Wonder movie is analyzed by using the context situations to find out the flow of each utterance from the speaker and listener. Researcher used the Pragmatic Approach and speech act theory to find out the types of illocutionary act contained in Wonder movie. And, from the result of this analysis, it was found that there are 5 types of illocutionary acts that classified by Searle (1975) in Wonder movie, that known as Representatives or Assertive, Directives, Comissives, Expressive and Declaration. Keywords: Movie / Film, Illocutionary, Pragmatic Approach.